A comparative Study of Interval and Non –Uniform Training Methods on Aerobic Capacity-An Experimental Study Conducted on ES Tissemsilt Handball Club. - Faiçal , Houafi (Journal of Sport Science Technology and Physical Activities, 2026)
The study aimed to examine the effect of interval and non-uniform training methods on aerobic capacity in U17 handball players. Using the experimental method, 24 players from ES Tissemsilt were randomly assigned to two groups. Data were collected via the YO-YO Test and analyzed statistically. Results showed positive effects for both training methods on aerobic capacity, with no significant difference, although interval training showed relative improvement. The study recommends tailoring training programs to players’ characteristics and using scientific assessment methods to monitor and improve aerobic fitness.